A história da disciplina de História Natural: prescrições, conteúdos e materiais (1890 – 1930) - Cameski, Andrezza Silva (2020)
This research understands that, at the end of the 19th century, there is an intense movement towards the establishment of scientific scholar subjects in Brazil, even though there is a predominance of the idea of classical humanities in the curriculum. This movement coincides with new ideals sought by the recently proclaimed Republic, which asks for scientific knowledge, constituting new school needs. The work seeks to investigate the course of constitution of the scholar subject called Natural History in the state of São Paulo, approaching the circulating knowledge and the knowledge produced in relation to secondary education, thinking about their prescriptions, contents and teaching materials. The central question is: how was Natural History constituted as a school discipline thinking about science education in its prescriptive character? The working hypothesis is that Natural History was constituted by a set of knowledge dialogued from an ideal of scientific science that circulated through natural history museums, the knowledge of naturalists, contents and materials designed in different spaces, the study of nature from the observation of which educational interests are not separated. For the study, documents located in the Arquivo Público de São Paulo, in the Arquivo Histórico da Assembleia Legislativa de São Paulo, in the Biblioteca do Livro Didático (BLD), in the Centro de Referência em Educação Mario Covas, in the Marista Arquidiocesano de São Paulo School and public schools in São Paulo: Gymnasio São Paulo and “Otoniel Mota” (Gymnasio de Ribeirão Preto), such as minutes of congregations, textbooks, scientific objects, crafts, newspapers, yearbooks, reports, legislation, etc. The history of school subject is studied in terms of its constitution, its objectives and its school practices, based on the studies of Chervel (1990), Goodson (1997, 2018) and Bittencourt (2003). Finally, as a result, we identified the idea of scientific education conceived for secondary education in Natural History through the use of scientific objects that sought to reproduce nature as close to reality as possible. Pieces that were used to provide the development of dedicated observation, which would allow the development of skills such as accurate description, data collection, analysis and conclusions from the experimentation of the concrete